Short-Term exposure to ambient air pollution and onset of work incapacity related to mental health conditions. (June 2022) - Bruyneel, Luk; Kestens, Wies; Alberty, Marc; Karakaya, Güngör; Van Woensel, Renata; Horemans, Christian; Trimpeneers, Elke; Vanpoucke, Charlotte; Fierens, Frans; Nawrot, Tim S; Cox, Bianca
Graphical abstract: Abstract: The OECD estimates that greater work absenteeism is one of the main drivers behind the impact of air pollution on gross domestic product loss, but research linking air pollution with work absenteeism is scarce. With air pollution increasingly being linked to poor mental health, and poor mental health having become one of the main reasons for work absenteeism, we examined whether the onset of work incapacity related to mental health conditions is associated with short-term fluctuations in ambient black carbon (BC), nitrogen dioxide (NO2 ), ozone (O3 ), and particulate matter 2.5 (PM2.5 ), estimating the contributions of these pollutants jointly, while accounting for relative humidity, total solar radiation and temperature. We conducted a bidirectional time-stratified case-crossover study with daily air pollution estimates by municipality linked with 12 270 events of work incapacity related to mental health conditions in 2019 in Belgium. We ran single- and multi-pollutant conditional logistic regression models for three different exposure windows (lag 0, 0–1 and 0–2), considering potential confounding by relative humidity and total solar radiation. We observed positive associations between work incapacity related to mental health conditions and BC, NO2, and O3 exposure, but findings for PM2.5 were inconsistent. Results from multi-pollutant models showed a 12% higher risk of work incapacity for an IQR increase in NO2 and O3 at the day of the event (lag 0), with estimates increasing to about 26% for average concentrations up to two days before the event (lag 0–2). We found evidence for effect modification by age and season in the association with NO2, with highest effect estimates in the age group 40–49 years and in spring and summer. For O3, we observed effect modification by type of mental health problem. This country-wide study suggests that air pollution aggravates within 48 h a likely existing propensity to enter work incapacity because of mental health conditions.